2014
DOI: 10.1002/2013jb010483
|View full text |Cite
|
Sign up to set email alerts
|

A fixed sublithospheric source for the late Neogene track of the Yellowstone hotspot: Implications of the Heise and Picabo volcanic fields

Abstract: The Heise and Picabo volcanic fields of eastern Idaho are part of the more extensive time-transgressive Yellowstone-Snake River Plain hotspot track. Calderas associated with these two silicic volcanic fields are buried under 1 to 3 km of younger basalt, so their locations and eruption record histories have been based on analysis of silicic units along the margins of the eastern Snake River Plain along with some limited geophysical data. A 1.5 km borehole penetrating through basalt into underlying silicic rocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(82 citation statements)
references
References 90 publications
(380 reference statements)
6
74
0
Order By: Relevance
“…Other drillholes have mostly encountered outflow deposits. For example, among numerous units encountered in core in the eastern SRP, the thickest was a 200-m-thick lava and the thickest ignimbrite was ~30 m (Anders et al, 2014). This core bottomed in rhyolite, allowing the potential for greater thickness beneath, but the recovered drillcore produced 9 different units over a thickness of ~360 m, consistent with an extra-caldera sequence.…”
Section: Mcdermitt: An Analog For the Central Snake River Plain?mentioning
confidence: 90%
See 1 more Smart Citation
“…Other drillholes have mostly encountered outflow deposits. For example, among numerous units encountered in core in the eastern SRP, the thickest was a 200-m-thick lava and the thickest ignimbrite was ~30 m (Anders et al, 2014). This core bottomed in rhyolite, allowing the potential for greater thickness beneath, but the recovered drillcore produced 9 different units over a thickness of ~360 m, consistent with an extra-caldera sequence.…”
Section: Mcdermitt: An Analog For the Central Snake River Plain?mentioning
confidence: 90%
“…At McDermitt the intermediate compositions are effusive, and so such compositions could have erupted in the younger systems but remain obscured within the poorly exposed calderas. However, two main lines of evidence argue against this: (1) no such intermediates are observed at Yellowstone where intracaldera lavas are abundant (Christiansen, 2001;Stelten et al, 2015), and (2) samples from drillcores in the CSRP exhibit the same basalt-rhyolite compositional bimodality as the surficial record (Anders et al, 2014;Knott et al, 2016). These petrologic differences may reflect different crustal environments, i.e., accreted terrane for the McDermitt caldera, and craton for the CSRP (Fig.…”
Section: Mcdermitt: An Analog For the Central Snake River Plain?mentioning
confidence: 99%
“…Previous gravity modeling [ DeNosaquo et al , ] revealed that the lowest density material extends ~20 km NE of the caldera (Figure S7b), similar to our Vp model, although our imaged anomaly is shallower than the low‐density anomaly NE of the Yellowstone caldera (Figure S7b). Importantly, the distance the Yellowstone hot spot would “migrate” due to the SW motion of the North American plate, at ~2.35 cm/yr [ Anders et al , ], since the last major Yellowstone eruption at 0.64 Ma shows an apparent NE migration of ~15 km which again is strikingly similar to the NE extent of the low‐velocity body imaged in this study. This suggests that the apparent NE migration of the Yellowstone hot spot over the last 640,000 years has fueled the crustal magma reservoir through new magma pathways NE of the caldera.…”
Section: Yellowstone 3‐d P Wave Velocity Model and Interpretationmentioning
confidence: 99%
“…The two ignimbrites only occur in stratigraphic contact in one outcrop where an ignimbrite correlated to the CCT (tuff of Elkhorn Spring; Morgan and McIntosh, 2005) overlies the WCT; however, this correlation has been questioned by Anders et al (2014) who instead proposed a reverse stratigraphic order based on 40 Ar/ 39 Ar dating of a drillcore located in the middle of the SRP. Both units have been extensively dated by both 40 Ar/ 39 Ar and U-Pb methods, with essentially indistinguishable ages ranging between 5.45-5.80 Ma for WCT and 5.51-6.01 Ma for CCT (Anders et al, 2014;Bindeman et al, 2007;Morgan and McIntosh, 2005;Nash et al, 2006).…”
Section: Wolverine Creek Tuff and Conant Creek Tuffmentioning
confidence: 99%
“…Both units have been extensively dated by both 40 Ar/ 39 Ar and U-Pb methods, with essentially indistinguishable ages ranging between 5.45-5.80 Ma for WCT and 5.51-6.01 Ma for CCT (Anders et al, 2014;Bindeman et al, 2007;Morgan and McIntosh, 2005;Nash et al, 2006). Finding such temporally close deposits in the SRP is unusual with typical repose periods between explosive eruptions ranging between 200-300 kyr during the 11.7-10.2 Ma 'ignimbrite flare-up' and much longer in the younger successions (Christiansen, 2001).…”
Section: Wolverine Creek Tuff and Conant Creek Tuffmentioning
confidence: 99%